Measuring the Effect of Problem Based Learning With Instructional Video on Primary School Students' Problem Solving Skills Development - Fitriati, Fitriati; Rahmi, Rahmi; Novita, Rita; Salmina, MIK; Sari, Intan Kemala; Nasriadi, Ahmad; Muzakir, Ully; Fajri, Nurul (Jurnal Ilmiah Teunuleh, 2023)
This study aims to analyse the efficacy of instructional video through problem-based learning model in developing problem-solving skills among primary school students. This research integrated in video instructional material related to statistics topics "data collection and data presentation" to improve student problem-solving skills. Quasi Post-test-only system experiment was used to achieve this study's goal. The model was introduced in three primary public schools in Banda Aceh, Indonesia, involving 163 grade 5 students. A post-examination test was administered after treatment. Independent t-test findings indicate a substantial mean difference between the control group and the experimental group with a significant level below 0.05. Accordingly, integrating classroom video collaboration with problem-based learning model helps students strengthen their understanding of statistics subject and enhance their problem-solving skills. Thus these findings suggest that PBL with instructional video is more successful than traditional teaching method to boost problem-solving ability among primary school students.